Probiotic treatment with ab-kolicare® causes Changes in the microbiota which correlate With a reduction in crying time - MARIA TINTORE; JORDI CUNE (International Journal of Pharma and Bio Sciences, 2017)
Growing interest is being placed on the role of intestinal microbiota as several studies have correlated alterations in diversity and abundance of relevant bacterial subpopulations with conditions without apparent etiology, such as infant colic. In this work, we study the changes in the microbiota of colicky infants induced by the treatment with AB-Kolicare, a probiotic formula comprised by Pediococcus pentosaceus CECT 8330 and Bifidobacterium longum CECT 7894. A significant increase in the microbiota diversity was found in infants treated with AB-Kolicare when compared to placebo, which correlated with a reduction in the total crying time. In addition, relative abundance of several phyla and genera which are described to be increased in colic was reduced after treatment, and a significant increase in the rate of subpopulations which protect against colic was also observed in comparison to placebo.